Skin autonomous antibody production regulates host-microbiota interactions - Gribonika, Inta ; 0000-0002-5694-1315; Band, Victor I; Chi, Liang; Perez-Chaparro, Paula Juliana; Link, Verena M; Ansaldo, Eduard; Oguz, Cihan; Bousbaine, Djenet; Fischbach, Michael A; Belkaid, Yasmine (Nature, 2025)
The microbiota colonizes each barrier site and broadly controls host physiology1. However, when uncontrolled, microbial colonists can also promote inflammation and induce systemic infection2. The unique strategies used at each barrier tissue to control the coexistence of the host with its microbiota remain largely elusive. Here we uncover that, in the skin, host-microbiota symbiosis depends on the ability of the skin to act as an autonomous lymphoid organ. Notably, an encounter with a new skin commensal promotes two parallel responses, both under the control of Langerhans cells. On one hand, skin commensals induce the formation of classical germinal centres in the lymph node associated with immunoglobulin G1 (IgG1) and IgG3 antibody responses. On the other hand, microbial colonization also leads to the development of tertiary lymphoid organs in the skin that can locally sustain IgG2b and IgG2c responses. These phenomena are supported by the ability of regulatory T cells to convert into T follicular helper cells. Skin autonomous production of antibodies is sufficient to control local microbial biomass, as well as subsequent systemic infection with the same microorganism. Collectively, these results reveal a compartmentalization of humoral responses to the microbiota allowing for control of both microbial symbiosis and potential pathogenesis.
© 2024. The Author(s).
Keywords: Animals; Skin/immunology; Mice; Immunoglobulin G/immunology; Microbiota/immunology; Symbiosis/immunology; Female; Male; Germinal Center/immunology; Host Microbial Interactions/immunology; T-Lymphocytes, Regulatory/immunology; Antibody Formation/immunology; Langerhans Cells/immunology; Mice, Inbred C57BL; Lymph Nodes/immunology; T Follicular Helper Cells/immunology